Answer:
Step-by-step explanation:
Let f(x) = x^7 - 4e^x .
Then f '(x) = 7x^6 - 4e^x, and
f "(x) = 42x^5 - 4e^x, and so:
f '(-1) = 7(-1)^6 - 4e^(-1) = 7 + 4/e
and
f "(x) = 42(-1)^5 - 4e^(-1) = -42 + 4/e
Solve this inequality: 36 - 7 < 32
You already did. That is a true statement.
32 > 29 [and vice versa]
I am joyous to assist you anytime.
The inequality 29 < 32 is true.
After calculating 36 - 7 which equals 29, we compare this result to 32. The inequality 29 < 32 holds true, so the original inequality 36 - 7 < 32 is correct.
The student has asked to solve the inequality 36 - 7 < 32. To solve this inequality, we need to perform the subtraction on the left side of the inequality first.
When we calculate 36 - 7, we get 29. Now we can compare this result to 32 to determine if the inequality holds true.
Since we are dealing with an inequality, we know that if a value a is less than a value b, then a is indeed smaller in quantity or value compared to b. Here, 29 is indeed less than 32. Therefore, the inequality 29 < 32 is true.
Find the value of x.
A. 1.1
B. 6.6
C. 8.8
D. 5.5
Answer:
B. 6.6Step-by-step explanation:
AC is a midsegment of the trapezoid DFBE.
The formula of a midsegment of trapezoid is:
[tex]m=\dfrac{a+b}{2}[/tex]
a, b - bases of a triangle
We have
a = x, b = 4.4, m = 5.5
Substitute:
[tex]5.5=\dfrac{x+4.4}{2}[/tex] multiply both sides by 2
[tex]11=x+4.4[/tex] subtract 4.4 from both sides
[tex]6.6=x\to x=6.6[/tex]
What is the midpoint of the segment shown below?
Answer:
A
Step-by-step explanation:
Calculate the midpoint using the midpoint formula
[ 0.5(x₁ + x₂ ), 0.5(y₁ + y₂ ) ]
with (x₁, y₁ ) = (- 1, 5) and (x₂, y₂ ) = (5, 5)
midpoint = [ 0.5(- 1 + 5), 0.5(5 + 5) ]
= [ 0.5(4), 0.5(10) ] = (2, 5 ) → A
Answer:
The answer would be A 2,5
Step-by-step explanation:
-8(5x+5)+9x(10x+9)=20
[tex]-8(5x+5)+9x(10x+9)=20\\-40x-40+90x^2+81x-20=0\\90x^2+41x-60=0\\\\\Delta=41^2-4\cdot90\cdot(-60)=1681+21600=23281\\\\x=\dfrac{-41\pm \sqrt{23281}}{2\cdot90}=\dfrac{-41\pm \sqrt{23281}}{180}[/tex]
The digits of a two-digit number sum to 8. When the digits are reversed, the resulting number is 18 less than the original
number. What is the original number?
Answer:
It's 53.
Step-by-step explanation:
Let the number be xy so the digits are x and y, so:
x + y = 8...........(1)
Reversing the 2 digits we have the number 10y + x and this equals
10x + y - 18 so we have the equation:-
10x + y - 18 = 10y + x
9x - 9y = 18
x - y = 2...........(2) Adding equations (1) and (2) we have:
2x = 10
x = 5
and y = 8 - 5 = 3.
So the original number is 53.
We can check this as follows
Original number is 53 so the reverse is 35 .
53 - 35 = 18 which checks out.
Which expression is equivalent to log3(x + 4)?
log3 - log(x + 4)
log12 + logx
log3 + log(x + 4)
log 3/log(x+4)
Answer:
log[3(x+4)] is equal to log(3) + log(x + 4), which corresponds to choice number three.
Step-by-step explanation:
By the logarithm product rule, for two nonzero numbers [tex]a[/tex] and [tex]b[/tex],
[tex]\log{(a \cdot b)} = \log{(a)} + \log{(b)}[/tex].
Keep in mind that a logarithm can be split into two only if the logarithm contains the product or quotient of two numbers.
For example, [tex]3(x + 4)[/tex] is the number in the logarithm [tex]\log{[3(x + 4)]}[/tex]. Since [tex]3(x + 4)[/tex] is a product of the two numbers [tex]3[/tex] and [tex](x + 4)[/tex], the logarithm [tex]\log{[3(x + 4)]}[/tex] can be split into two. By the logarithm product rule,
[tex]\log{[3(x + 4)]} = \log{(3)} + \log{(x + 4)}[/tex].
However, [tex]\log{(x + 4)}[/tex] cannot be split into two since the number inside of it is a sum rather than a product. Hence choice number three is the answer to this question.
Answer:
c
Step-by-step explanation:
Use the graph of f(x) to evaluate the following:
The average rate of change of f from x=0 to x=4 is_____.
Give your answer as an integer or reduced fraction
Answer:
-5/4
Step-by-step explanation:
The average rate of change of f from x=0 to x=4 is_____.
This means we are being asked to evaluate [tex]\frac{f(4)-f(0)}{4-0}[/tex].
To do this we will need to find f(0) and f(4).
f(0) means what y-coordinate corresponds to x=0 on the curve. Find x=0, the curve is above there, go straight up and see y=5 there. This means f(0)=5.
f(4) means what y-coordinate corresponds to x=4 on the curve. Find x=4, then curve is above there, go straight up and see y=0 there. This means f(4)=0.
So we have:
[tex]\frac{f(4)-f(0)}{4-0}=\frac{0-5}{4-0}=\frac{-5}{4}[/tex].
What is the solution to 2x-8 <12?
Answer:
[tex]x < 10[/tex]
Step-by-step explanation:
[tex]2x - 8 < 12 \\ 2x - 8 + 8 < 12 + 8 \\( 2x < 20) \div 2 = x < 10[/tex]
x<10 is the solution to the inequality 2x - 8 < 12
To solve the inequality 2x - 8 < 12, you can follow these steps:
Add 8 to both sides of the inequality:
2x - 8 + 8 < 12 + 8
This simplifies to:
2x < 20
Divide both sides of the inequality by 2:
(2x)/2 < 20/2
This simplifies to:
x < 10
Therefore, the solution to the inequality 2x - 8 < 12 is x < 10.
Learn more about inequalities here:
https://brainly.com/question/30231190
#SPJ6
Find the Inverse of this function f(x)={(3,4),(4,3),(-2,6)}
as you may already know, the inverse of a function has the same exact x,y pairs but backwards, namely f(x)'s domain is f⁻¹(x)'s range.
[tex]\bf \stackrel{f(x)}{\begin{array}{|cc|ll} \cline{1-2} \stackrel{domain}{x}&\stackrel{range}{y}\\ \cline{1-2} 3&4\\ 4&3\\ -2&6\\ \cline{1-2} \end{array}}~\hspace{10em} \stackrel{inverse~of~f(x)}{\begin{array}{|cc|ll} \cline{1-2} \stackrel{domain}{x}&\stackrel{range}{y}\\ \cline{1-2} 4&3\\ 3&4\\ 6&-2\\ \cline{1-2} \end{array}}[/tex]
4x – 9y = 7
–2x + 3y = 4
What number would you multiply the second equation by in order to eliminate the x-terms when adding to the first equation?
Answer:
By 2.
Step-by-step explanation:
You need to eliminated the x-terms, so the first step is to focus only in those terms.
So yo have 4x and -2x, since you are thinking in eliminate then you have this equation>
[tex]4-2*K=0[/tex]
Note that we dont put the x variable, since we are studying its coefficients in the equations system.
Solving for K, Gives us that K=2
So.
Multiplying the second equation by 2 results in
[tex]-4x+6y=8[/tex]
When you put them together, it gives you the following
[tex]4x-9y -4x+6y- 7+8[/tex]
and the final equation is
[tex]-3y=15\\[/tex]
giving you the answer for y, that is [tex]y=-5[/tex]
Answer: 2 and 3.
Step-by-step explanation:
Which properties of equality are used to solve the following (in no particular order)?
3(x + 12) - 2 = 50
Addition Property of Equality
Subtraction Property of Equality
Division Property of Equality
Combine Like Terms
Distributive Property
All except combine like terms. Since you only have 1 variable.
Hope this helps.
r3t40
Write an equation in a point-slope form that passes through the given point with the given slope (3, 5), m = -4 and-1, 8), m = ½
Answer:
[tex]\large\boxed{y-5=-4(x-3)}\\\boxed{y-8=\dfrac{1}{2}(x+1)}[/tex]
Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
[tex]m=-4,\ (3,\ 5)\\\\y-5=-4(x-3)[/tex]
[tex]m=\dfrac{1}{2},\ (-1,\ 8)\\\\y-8=\dfrac{1}{2}(x-(-1))\\\\y-8=\dfrac{1}{2}(x+1)[/tex]
In circle O, AD and BE are diameters. What is m? 106° 132° 138° 164°
Answer:
It is 132 just took it
Step-by-step explanation:
Each of the pairs of opposite angles made by two intersecting lines is called a vertical angle. The measure of ∠AOE is 132°. The correct option is B.
What are vertical angles?Each of the pairs of opposite angles made by two intersecting lines is called a vertical angle.
In circle O, AD and BE are diameters. Also, the measure of ∠EOD and ∠AOB will be equal because the two angles are vertically opposite angles. Therefore,
∠EOD = ∠AOB = 3x
As it is given that the measure of ∠AOC is 90°. Therefore, we can write,
∠AOC = ∠AOB + ∠BOC
90 = 3x + 0.5x + 34
56 = 3.5x
x = 16
Now, the measure of ∠EOD will be,
∠EOD = 3x
∠EOD = 3(16°)
∠EOD = 48°
Further, we can write,
∠AOD = ∠AOE + ∠EOD
180° = ∠AOE + 48°
∠AOE = 132°
The complete question is mentioned in the below image.
Learn more about Vertical Angles:
https://brainly.com/question/24460838
#SPJ2
in 135 space shuttle missions, there were two failures. Based on these data, what's the probability of a successful mission?
Answer:
98.518 repeating prercent
Step-by-step explanation:
2 out of 135 can also be written as 2/135
2 divided by 135 is 0.014814814814
that number is the percentage of failures
100% in decimal form is 1.00
1.00 subtracted by the percentage of failures is the percentage of successes
which is .98518518518, 518 repeating move the decimal over 2 and you got the percentage 98.518 repeating
A group of students and workers entering a metro station
were asked whether they were riding the bus or the
subway. The two-way table shows their answers.
Types of Transportation
Bus
Subway
Students
Workers
Total
166
27 + 42 + 21 + 76 = 166
Which one of the following equations could describe the graph above?
Answer: A. y=(1/2)^x+6
Step-by-step explanation: If this is the graph you’re talking about-
When “a” is less than one, the graph increases exponentially to the left. The smaller the value of a, the steeper the slope of the line.
There is a vertical shift up 6 as well
Events A and B are disjointed.
P(A) = 4/11 ; P(B) = 3/11.
Find P(A or B).
*Answer Options*
7/11
4/11
3/11
8/11
Answer:
7/11
Step-by-step explanation:
Two events are disjoint events if they cannot occur at the same time. It is given that A and B are disjointed events, so A and B cannot occur at the same time i.e. the intersection of two disjoint events will be 0.
For two disjoint events A and B:
P(A or B) = P(A) + P(B)
P(A) is given to be 4/11 and P(B) is given to be 3/11. Using these values in the equation, we get:
P(A or B) = [tex]\frac{4}{11}+\frac{3}{11} = \frac{3+4}{11}=\frac{7}{11}[/tex]
What is the length of the hypotenuse in the right triangle shown below?
Answer:
C. 6√2.
Step-by-step explanation:
Since this is a right angled isosceles triangle bot legs are 6 units long
So h^2 = 6^2 + 6^2 = 72
h = √72 = 6√2.
Answer:
The correct option is C) 6√2.
Step-by-step explanation:
Consider the provided triangle.
The provided triangle is a right angle triangle, in which two angles are 45° and one is 90°.
As both angles are equal there opposite side must be equal.
Thus, the leg of another side must be 6.
Now find the hypotenuse by using Pythagorean theorem:
[tex]a^2+b^2=c^2[/tex]
Substitute a = 6 and b = 6 in [tex]a^2+b^2=c^2[/tex].
[tex](6)^2+(6)^2=(c)^2[/tex]
[tex]36 + 36=(c)^2[/tex]
[tex]72=(c)^2[/tex]
[tex]6\sqrt{2}=c[/tex]
Hence, the length of the hypotenuse in the right triangle is 6√2.
Therefore, the correct option is C) 6√2.
[tex] - 3 + 5i \div - 3 - 4i[/tex]
Answer:
[tex]\frac{-11}{25}+\frac{-27}{25}i[/tex] given you are asked to simplify
[tex]\frac{-3+5i}{-3-4i}[/tex]
Step-by-step explanation:
You have to multiply the numerator and denominator by the denominator's conjugate.
The conjugate of a+bi is a-bi.
When you multiply conjugates, you just have to multiply first and last.
(a+bi)(a-bi)
a^2-abi+abi-b^2i^2
a^2+0 -b^2(-1)
a^2+-b^2(-1)
a^2+b^2
See no need to use the whole foil method; the middle terms cancel.
So we are multiplying top and bottom of your fraction by (-3+4i):
[tex]\frac{-3+5i}{-3-4i} \cdot \frac{-3+4i}{-3+4i}=\frac{(-3+5i)(-3-4i)}{(-3-4i)(-3+4i)}[/tex]
So you will have to use the complete foil method for the numerator. Let's do that:
(-3+5i)(-3+4i)
First: (-3)(-3)=9
Outer:: (-3)(4i)=-12i
Inner: (5i)(-3)=-15i
Last: (5i)(4i)=20i^2=20(-1)=-20
--------------------------------------------Combine like terms:
9-20-12i-15i
Simplify:
-11-27i
Now the bottom (-3-4i)(-3+4i):
F(OI)L (we are skipping OI)
First:-3(-3)=9
Last: -4i(4i)=-16i^2=-16(-1)=16
---------------------------------------------Combine like terms:
9+16=25
So our answer is [tex]\frac{-11-27i}{25}{/tex] unless you want to seprate the fraction too:
[tex]\frac{-11}{25}+\frac{-27}{25}i[/tex]
7.
chef has 50 pounds of strip Zebra. The trim loss on the strip zebra is
40% and the cooking loss is 60% of the trimmed weight. How many
pounds of trimmed, cooked strip zebra will the chef have left to serve to
his customers?
Answer:
12 pounds
Step-by-step explanation:
After trimming:
50 − 0.40 (50) = 0.60 (50) = 30
After cooking:
30 − 0.60 (30) = 0.40 (30) = 12
Let f(x) = 4x - 7 and g(x) = 2x - 3. Find (fog)(4).
Answer:
13
Step-by-step explanation:
(f∘g)(4) is another way of writing f(g(4)).
First, find g(4).
g(x) = 2x − 3
g(4) = 2(4) − 3
g(4) = 5
Now substitute into f(x).
f(x) = 4x − 7
f(g(4)) = 4g(4) − 7
f(g(4)) = 4(5) − 7
f(g(4)) = 13
[tex](f\circ g)(x)=4(2x-3)-7=8x-12-7=8x-19\\\\(f\circ g)(4)=8\cdot4-19=13[/tex]
Two tins are geometrically similar. If the ratio of their volume is 27:64 find the ratio of their curved surface area.
Answer:
9 : 16
Step-by-step explanation:
Given 2 similar figures with linear ratio = a : b, then
area ratio = a² : b² and
volume ratio = a³ : b³
Here the volume ratio = 27 : 64, hence
linear ratio = [tex]\sqrt[3]{27}[/tex] : [tex]\sqrt[3]{64}[/tex] = 3 : 4
Hence area ratio = 3² : 4² = 9 : 16
16. The dimensions of a window are 3x + 10 and 2x + 6. What is the area of the window?
Answer:
Answer in factored form (3x+10)(2x+6)
Answer in standard form 6x^2+38x+60 ( I bet you they want this answer)
Step-by-step explanation:
The assumption is this is a rectangle.
If you have the dimensions of a rectangle are L and W, then the area is equal to L times W.
So here we just need to multiply (3x+10) and (2x+6).
The answer in factored form is (3x+10)(2x+6).
I bet you they want the answer in standard form.
So let's use foil.
First: 3x(2x)=6x^2
Outer: 3x(6)=18x
Inner: 10(2x)=20x
Last: 10(6)=60
----------------Add up!
6x^2+38x+60
The area of the window is 3x² + 19x + 30
The dimension of the window are 3x + 10 and 2x + 6.
The area of the window can be calculated as follows;
area = lw
Therefore,
area = (3x + 10)(2x + 6)
area = 6x² + 18x + 20x + 60
area = 6x² + 38x + 60
area = 3x² + 19x + 30
read more: https://brainly.com/question/3518080?referrer=searchResults
Rowena walks 3 kilometers a day. How many meters does she walk in three days?
[tex]\huge{\boxed{\text{9,000 meters}}}[/tex]
There are 1,000 meters in each kilometer, so multiply to find the daily number of meters. [tex]3*1000=3000[/tex]
Multiply this by 3 to find the number of meters Rowena walks in three days. [tex]3000*3=\boxed{9000}[/tex]
What is 7(x+6)=3(x+9)
Answer:
x= -3.75
Step-by-step explanation:
Answer:
x = -15/4
Step-by-step explanation:
7(x+6)=3(x+9)
Distribute
7x+42 = 3x+27
Subtract 3x from each side
7x-3x+42 = 3x-3x+27
4x +42 = 27
Subtract 42 from each side
4x+42-42 = 27-42
4x =-15
Divide each side by 4
4x/4 =-15/4
x = -15/4
Which represents a perfect cube?
8.8.8
8+8+8
9.9.9.9
9+9+9+9+9
Answer:
8.8.8.
Step-by-step explanation:
8.8.8 = 8^3 = 512 Perfect cube.
8+8+8 =24
9.9.9.9 = 6561
9+9+9+9+9 = 45.
None of the others are perfect cubes.
Answer:A 8.8.8
Step-by-step explanation:i did the quiz
If Sn=n^2+3 then t10=?
Answer:
T10= -21
Step-by-step explanation:
If Sn=n^2+3 then t10=?
Sn= n²+5
put n=1, 2
S1= T1 = (1)²+5
=1+5 =6
S2= n²+5
S2=(2)²+5
S2=4+5
S2=9
T2 = S2 - S1
T2 = 9-6
T2=3
T10 = a+(n-1)d
where a = 6, d = -3, n=10
T10= 6+(10-1)*-3
T10=6+(9)*-3
T10=6+(-27)
T10=6-27
T10= -21
Therefore T10= -21 ....
Need The Answer Plz And Thank You!! I’m Failing
Angle BCA
Step-by-step explanation:
You can see this due to the angle having the name amount of congruent angle marks.
When solving -1/5 (x − 25) = 7, what is the correct sequence of operations?
A:Multiply each side by negative one over five , add 25 to each side
B:Multiply each side by 5, subtract 25 from each side
C:Multiply each side by negative one over five , subtract 25 from each side
D;Multiply each side by −5, add 25 to each side
Answer:
It is C. Multiply each side by negative one over five , subtract 25 from each side.
Hope this helped you! :3
Answer:
D;Multiply each side by −5, add 25 to each side
Step-by-step explanation:
-1/5 (x − 25) = 7
To solve this equation, we will first multiply both-side of the equation by -5
-5 × -1/5(x-25) =7 × 5
(At the left-hand side of this equation, the 5 we multiplied will cancel the 5 at the denominator, leaving us with just '1' since negative multiply by negative is positive), Hence our equation becomes;
(x - 25) = 35
x - 25 = 35
Then the next thing to do is to add 25 to both-side of the equation in other to get the value of your x
x -25 + 25 = 35 + 25
x=60
Therefore, option D is the correct sequence of operation to follow to enable you solve the equation.
HELPPPP WILL NAME BRAINIEST
Answer:
Triangle APB is an isosceles triangle ⇒ 3rd answer
Step-by-step explanation:
* Lets explain the how to solve the problem
- ABCD is a square
∴ AB = BC = CD = AD
∴ m∠A = m∠∠B = m∠C = m∠D = 90°
- DPC is equilateral triangle
∴ DP = PC = DC
∴ m∠DPC = m∠PCD = m∠CDP = 60°
- In the Δs APD , BPC
∵ AD = BC ⇒ sides of the square
∵ PD = PC ⇒ sides of equilateral triangle
∵ m∠ADB = m∠BCP = 30° (90° - 60° = 30) ⇒ including angles
∴ Δs APD , BPC are congregant ⇒ SAS
- From congruent
∴ AP = BP
∴ Triangle APB is an isosceles triangle